(untitled) (Journal of Engineering, 2024)
The main purpose of this study is to investigated the single fillet weld design for built-up members by using ftision welding and find the effects of welding power input on that design for member. In this work, investigation of welding metal for Low carbon steel plate type St.52-3, thickness 6-8 rnm, which is to ensure good mechanical properties under high stresses for ( Welding metal , heat affected Zone (HAZ) and base metal ). Also it can be explain, that the effects of welding processes on the deformation and changes in mechanical and metallurgical properties due to high thermal energy, results from welding process. This study involved: weld design, selection of suitable electrode, evaluation of mechanical and metallurgical properties, the maximum allowable value of sweep of welded mamber after ( fabrication and erection ) has been calculated, also leg and through length have been calculated for the welded Zone. The main results of this study are : - The value of sweep which occur before the erection and tightening is ( 29 mm. ). - The leg and through length of welding metal which welded by electrode type ( E 7018 = OKUS ), its found equal to ( 4 mm. ). The study results can ensure good mechanical and metallurgical properties for signal filled weld ( Built-up members ). ’ i